2008
DOI: 10.1136/adc.2007.125062
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric acute asthma management in Australia and New Zealand: Practice patterns in the context of clinical practice guidelines

Abstract: CPG recommendations and reported physician practice for mild to moderate paediatric asthma management were broadly similar across PREDICT sites and consistent with national guidelines. Practice was highly variable for severe to critical asthma and probably reflects limitations of available evidence. Areas of controversy, in particular the comparative efficacy of intravenous bronchodilators, would benefit from multi-centre trials. Collaborative development of CPGs should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 43 publications
(51 reference statements)
0
45
0
1
Order By: Relevance
“…3 The use of MDIs with holding chambers offers several advantages, including potential cost efficiencies and improved patient health care experience (Table 1). Yet surveys of pediatric acute care settings in various Western countries continue to show that nebulization remains the dominant method for b-agonist inhalation administration, [11][12][13][14][15][16] despite convincing evidence and recommendations in national and international asthma care guidelines. 14,[17][18][19] In 2006, a qualitative study at our study site identified perceived barriers to changing the method of salbutamol inhalation delivery.…”
Section: Ré Sumémentioning
confidence: 99%
“…3 The use of MDIs with holding chambers offers several advantages, including potential cost efficiencies and improved patient health care experience (Table 1). Yet surveys of pediatric acute care settings in various Western countries continue to show that nebulization remains the dominant method for b-agonist inhalation administration, [11][12][13][14][15][16] despite convincing evidence and recommendations in national and international asthma care guidelines. 14,[17][18][19] In 2006, a qualitative study at our study site identified perceived barriers to changing the method of salbutamol inhalation delivery.…”
Section: Ré Sumémentioning
confidence: 99%
“…Most gave the BTS/SIGN salbutamol MDI dose, though some tended towards lower doses in younger children. Ipratropium bromide use is more varied as in other healthcare systems, perhaps due to conflicting literature 13. However, in a recent systematic review, children treated with ipratropium bromide and salbutamol compared with salbutamol alone have lower rates of hospital admission, nausea and tremor and greater improvement in lung function 17…”
Section: Discussionmentioning
confidence: 99%
“…Many recommendations derive from high quality studies, but some are based on lesser evidence or expert consensus. Paucity of evidence results in guidance which cannot provide detail in some areas, potentially leading to individual interpretation and practice variation as in other systems 12 13. This may contribute to differences in admission rates, bed days and length of stay across English primary care trusts 5…”
Section: Introductionmentioning
confidence: 99%
“…The huge differences in doses for adults and children are inconsistent with the predicted similarity in their salbutamol PK-PD relationship. More importantly, higher doses could translate to an increased risk of toxic reactions, and the inconsistencies in dosing regimens are liable to engender uncertainty and confusion among clinicians 25 26. For example, using dosing regimens recommended by the BNFc, a child weighing 20 kg and over 2 years of age will receive the same intravenous bolus dose as that recommended for a 70 kg adult 4 5.…”
Section: Intravenous Salbutamol Dosing Recommendations For Adultsmentioning
confidence: 99%